Sales Force Automation (SFA) / Tai Ching Han - Tai, Ching Han (2002)
This project focuses on the development of sales application in the market; named ' Sales Force Automation' or for short ' SFA', which also acts as a tool to create and manage marketing campaigns with costs and performance tracking capabilities. It also can define as a Customer Relationship Management system. Sales Force Automation (SFA) is an application service provider that focuses on providing and hosting applications related exclusively to business functions. [tallows the company to forecast revenues accurately, possesses a clear, reliable understanding of near-term future events, and can focus their resources accordingly. Microsoft Visual Studio.NET - ASP.NET, is to develop this application. Sales Force Automation database will store in Microsoft SQL Server 2000, and others tools or software are used to design SF A. They are Adobe Photoshop 7 .O. Macromedia Flash :MX and Swish 2.0. In conclusion, my project will help the users to developing and implementing business strategies and supporting technologies that close the gaps between an organization's current and potential performance in customer acquisition, growth, and retention.